SERVICE-EXCELLENT GUEST REVIEW OLEH FRONT OFFICE HOTEL SEBAGAI STRATEGI MEMPERTAHANKAN LOYALITAS TAMU - Riani Ishak; Sri Endah Yuwantiningrum; Samuel (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2023)
This research focuses on analyzing customer complaint management strategies through online reviews at the favehotel Padjadjaran in Bogor City in an effort to maintain guest loyalty so that excellent service is in accordance with the corporate values promoted by the hotel towards customers. The aim of this research is to analyze the handling of customer complaints at the favehotel Padjajaran hotel, Bogor city, by the Front Office Division. The research method is qualitative-descriptive which uses observation, interviews (in-depth interviews) and documentation for data collection supported by library research, where the data sources studied in this research are reference books and scientific articles from journals. The data sources in this research are the hotel manager, Front Office Manager, other division managers, FO supervisors, and the front desk staff team. The results of the collected data are described descriptively. The results obtained in this research indicate that handling customer reviews and complaints submitted online and offline can be done using various methods. Identification of the type of complaint determines the appropriate method that should be applied. The skill of handling online reviews quickly needs to be mastered by the Hotel Front Office in order to retain guests to want to stay again. Therefore, increasing positive ratings (reviews) of hotels is the obligation of the hotel front office. In an effort to provide excellent service to customers so that customers remain loyal. The application of the ILEAD and HEAT methods is still appropriate for handling offline complaints, and the RIFD method is more appropriate for handling online complaints and reviews at favehotel Padjajaran Bogor.